Osmotic and ionic regulation in Nitella - Nakagawa, Shigeo; Kataoka, Hironao; Tazawa, Masashi (Oxford University Press, 1974)
When the osmotic value of an internodal cell of Nitella flexilis was modified by the method of transcellular osmosis, the normal osmotic value was chiefly restored by the release or absorption of K+. The release or uptake of Na+ was observed only when the modification of osmotic value was significant. Both the uptake and release of K+ were linearly dependent on the degree of modification of the osmotic value. The effectiveness of alkali metal cations in restoring the osmotic value in cells of lower osmotic values was in the order K+>Rb+>Na+, Cs+>Li+. The absorption of K+ by cells of lower osmotic values depended strongly on temperature, while the release of K+ from cells of higher osmotic values did not. To clarify whether the Nitella cell regulates the osmotic value or regulates the concentration of K+ in the vacuole, the cell sap was exchanged for artificial cell saps whose osmotic values and ionic concentrations were varied independent of each other. It was shown that in Nitella two regulating mechanisms are operating, one which regulates the osmotic value of the cell sap irrespective of the level of vacuolar K+ (0.1–140 mM) and another which regulates the vacuolar K+-level when it is abnormaly high (>160 mM). Both mechanisms are assumed to operate in order to keep the concentration of K+ in the cytoplasm at a constant level. The presence of Na+ (0–100 mM) and Ca2+ (5–40 mM) did not affect the movement of K+ during osmoregulation.